Joseph A. Yablonski legal case collection
Legal records, U.S. Federal Bureau of Investigation files, crime scene photographs, and other records relating to the murder of labor leader Joseph A. Yablonski, his wife, Margaret Yablonski, and daughter, Charlotte Yablonski, and to the Pennsylvania state and federal trials of United Mine Workers of America president William Anthony Boyle, who ordered the murders, and his co-conspirators.
Full name: Joseph Albert Yablonski. Labor leader in the United Mine Workers of America.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Boyle, William Anthony, -- 1904-1985 -- Trials, litigation, etc; Yablonski, Charlotte, -- 1944 or 1945-1969.; Yablonski, Joseph A., -- 1910-1969.; Yablonski, Margaret, -- 1912 or 1913-1969.; United States. -- Federal Bureau of Investigation; United Mine Workers of America; Labor leaders -- United States; Labor unions -- United States; Murder -- Pennsylvania; Trials (Murder) -- Pennsylvania; Trials (Murder) -- United States